Design of machinery : an introduction to the synthesis and analysis of mechanisms and machines - Norton, Robert L. (McGraw-Hill series in mechanical engineering., 1992)
This book presents an introduction to the synthesis and analysis of mechanisms and machines in Design of Machinery.